Remote sensing of unhelpful resilience to sea level rise caused by mangrove expansion: A case study of islands in Florida Bay, USA. (February 2019) - Zhai, Lu; Zhang, Bo; Roy, Shouraseni Sen; Fuller, Douglas O.; da Silveira Lobo Sternberg, Leonel
Highlights: Unhelpful resilience caused by mangrove expansion were detected by remote sensing based indicators. Florida Bay islands showed increased area under SLR. Florida Bay islands showed mangrove expansion contributing to the island resilience. Part of the mangrove expansion were at the expense of non-mangrove habitats. Abstract: Previous studies have found that vegetated coastal areas can increase their elevation indicating resilience to inundation by sea level rise (SLR), but the potential resilience were ignored or showed controversial results (i.e., soil accretion of vegetated areas vs . SLR). To estimate the resilience influences on 15 islands in Florida Bay (Florida, U.S.), our study used indicators (areas of the 15 islands and their mangrove forests) by analyzing 61-yr high-resolution historical aerial photographs and a 27-yr time-series of Landsat images. In these islands, coastal fringes are dominated by mangroves, and inland parts are dominated by brackish or freshwater species. Our results showed that: (1) despite rising sea levels, these low-lying islands significantly increased in area; (2) all of these islands had significant mangrove expansion, and the landward part of expansion led to the replacement of inland non-mangrove habitats; (3) there was a positive relationship between the increase of island area and mangrove expansion in these islands; (4) without the mangrove expansion, simulations showed that all of the islands had decreased areas by 2014 compared with that in 1953. On the basis of our spatial analyses and previous field studies in our study areas, these islands showed resilience to inundation and the mangrove expansion contributed to processes stabilizing these islands under SLR. Meanwhile, the mangrove expansion were partly at the expense of the habitats previously covered by non-mangrove species, thus potentially leading to a loss of plant diversity. Therefore, the mangrove expansion increased unhelpful resilience to maintain islands in a degraded state losing biodiversity, which should be considered in conservation accounting for future SLR. Moreover, the unhelpful resilience can be monitored by remote sensing based indicators, such as island area.